Udar niedokrwienny mózgu - postępowanie przedszpitalne i wczesnoszpitalne = Ischemic stroke - the procedure prehospital and hospital - Joanna Siminska; Katarzyna Pietkun; Piotr Porzych; Iwona Głowacka; Sebastian Grzyb; Wojciech Hagner; Kinga Grobelska; Krystyna Nowacka (Kazimierz Wielki University, 2016)
Siminska Joanna, Pietkun Katarzyna, Porzych Piotr, Głowacka Iwona, Grzyb Sebastian, Hagner Wojciech, Grobelska Kinga, Nowacka Krystyna. Udar niedokrwienny mózgu - postępowanie przedszpitalne i wczesnoszpitalne = Ischemic stroke - the procedure prehospital and hospital. Journal of Education, Health and Sport. 2016;6(8):439-453. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60875 http://ojs.ukw.edu.pl/index.php/johs/article/view/3779       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016.     UDAR NIEDOKRWIENNY MÓZGU - POSTĘPOWANIE PRZEDSZPITALNE I WCZESNOSZPITALNE   ISCHEMIC STROKE - THE PROCEDURE PREHOSPITAL AND HOSPITAL   Siminska Joanna1, Pietkun Katarzyna1,2, Porzych Piotr1, Głowacka Iwona1, Grzyb Sebastian3, Hagner Wojciech1, Grobelska Kinga4, Nowacka Krystyna1   1 Katedra i Klinika Rehabilitacji Collegium Medicum w Bydgoszczy 2 Katedra Kosmetologii i Dermatologii Estetycznej Collegium Medicum w Bydgoszczy 3 Klinika Neurochirurgii i Neurotraumatologii i Neurochirurgii Dziecięcej Collegium Medicum w Bydgoszczy 4 Klinika Medycyny Ratunkowej  Collegium Medicum w Bydgoszczy     Streszczenie Choroby naczyniowe ośrodkowego układu nerwowego są jednym z głównych problemów  zdrowotnych społeczeństwa XXI wieku, według niezadowalających prognoz statystycznych  szósty dorosły mieszkaniec globu dozna w swoim życiu udaru mózgu. Udar niedokrwienny mózgu jest jednostką chorobową, która stanowi jeden z najpoważniejszych problemów współczesnego ratownictwa medycznego jak i medycyny.  Dane epidemiologiczne wskazują, że często odwlekany jest moment wezwania zespołu ratownictwa medycznego od czasu zaistnienia pierwszych objawów udaru niedokrwiennego  mózgu. Analizy statystyczne przedstawiają, że ponad połowa chorych, która doświadczyła incydentu udarowego, w procesie kompleksowego leczenia wymaga długotrwałej hospitalizacji.   Mimo dużego rozwoju jaki dokonał się w medycynie, nadal konieczne jest rozszerzenie wiedzy na temat symptomów i leczenia udarów niedokrwiennych mózgu. Wiedza ta przyczyni się do zmniejszenia śmiertelności pacjentów jak również do szybszego podjęcia odpowiedniego leczenia.   Słowa kluczowe: udar niedokrwienny mózgu, medycyna ratunkowa, postępowanie ratunkowe.   Summary Vascular diseases of the central nervous system is one of the major health problems of society XXI century, according to statistical forecasts disappointing sixth adult inhabitant of the globe will experience in your life stroke. Ischemic stroke is a disease that is one of the most serious problems of modern medical rescue as and medicine. Epidemiological data indicate that often delayed the moment of the call emergency medical team since the occurrence of the first symptoms of stroke. Statistical analyzes show that more than half of the patients who experienced an incident of impact, in the process of a comprehensive treatment requires prolonged hospitalization. Despite the large development that has taken place in medicine, it is still necessary to increase knowledge about the symptoms and treatment of ischemic stroke. This knowledge will help to reduce mortality of patients as well as to quickly take appropriate treatment.   Keywords: ischemic stroke, emergency medicine, emergency procedures.